Migraine Prevention with Erenumab: Focus on Patient Selection, Perspectives and Outcomes - De Matteis E; Sacco S; Ornello R (Dove Medical Press, 2022)
Eleonora De Matteis, Simona Sacco, Raffaele Ornello Neuroscience Section, Department of Applied Clinical Sciences and Biotechnology, University of L'Aquila, L'Aquila, ItalyCorrespondence: Simona Sacco, Department of Applied Clinical Sciences and Biotechnology, University of L'Aquila, Via Vetoio, L'Aquila, 67100, Italy, Tel +39 0862433561 ; +39 0863499734, Email simona.sacco@univaq.itAbstract: Erenumab is a monoclonal antibody targeting the calcitonin gene-related peptide (CGRP) receptor suitable for episodic and chronic migraine prevention. Randomized clinical trials proved the superiority of erenumab to placebo in a strictly selected population, while real-world studies confirmed treatment efficacy in more severe forms of disease - most patients suffered from chronic migraine with medication overuse headache, had prior treatment failures, and long disease duration. According to guidelines, anti-CGRP pathway monoclonal antibodies should be reserved to patients who failed or have contraindication to several classes of preventive treatments. However, their ease of use, tolerability and efficacy make these monoclonal antibodies ideally suitable for most patients with migraine; cost-effectiveness needs to be considered when looking at expanding current prescription criteria. Also, data from open label extensions of randomized control trials confirmed sustained benefits of prolonged treatment up to 5 consecutive years without significant risk of adverse events. Further studies will provide insights on optimal treatment duration to achieve migraine remission and predictors of treatment response. In the present work, we aimed at reviewing design and results of the main studies on erenumab and discussing treatment use in the current migraine prevention scenario; we also summarized the main ongoing research projects and provided clinical perspectives for the future.Keywords: erenumab, migraine, real-world, randomized clinical trials, RCTs